Proposal for a new N-stage classification system for intrahepatic cholangiocarcinoma - Liao, Shan; Liao, Ruizhe; Wu, Huaxing; Wang, Shijie; Zhou, Yanming (Frontiers in Oncology, 2023)
Background The number of metastatic lymph nodes (MLNs) is not considered in the nodal status (N classification) of intrahepatic cholangiocarcinoma (ICC) in the current 8thEdition of the American Joint Committee on Cancer (AJCC) staging system. The aim of this study was to find out the optimal cut-off point based on the number of MLNs and establish a modified AJCC staging system for ICC according to the new N category Methods A total of 675 ICC patients diagnosed between 2004 and 2015 were retrieved from the Surveillance, Epidemiology and End Results (SEER) database. The optimal cut-off value of MLNs affecting survival was determined by X-tile software. The relative discriminative power was assessed by Harrell’s concordance index (C-index) and Akaike information criterion (AIC). Results The proposed new nodal category subdivided patients into three groups (N0, no MLN; N1, 1–3 MLNs; and N2, ≥ 4 MLNs) with significantly different overall survival (P < 0.001). Multivariable analysis revealed that the new nodal category was an independent prognostic factor (P < 0.001). Both the C-index and AIC for our modified staging system were better than those for the 8th AJCC edition (0.574 [95% confidence interval 0.533-0.615] versus 0.570 [95% confidence interval 0.527-0.613], and 853.30 versus 854.21, respectively). Conclusion The modified AJCC staging system based on the number of MLNs may prove to be a useful alternative for predicting survival of ICC patients in clinical practice.